Reinforcement of Asphalt Concrete by Polyester Fibers to Improve Flexural Bending Fatigue Resistance (Journal of Engineering, 2015)
Reinforcing asphalt concrete with polyester fibers considered as an active remedy to alleviate the harmful impact of fatigue deterioration. This study covers the investigation of utilizing two shapes of fibers size, 6.35 mm by 3.00 mm and 12.70 mm by 3.00 mm with mutual concentrations equal to 0.25 %, 0.50 % and 0.75 % by weight of mixture. Composition of asphalt mixture consists of different optimum (40-50) asphalt cement content, 12.50 mm nominal aggregate maximum size with limestone dust as a filler. Following the traditional asphalt cement and aggregate tests, three essential test were carried out on mixtures, namely: Marshall test (105 cylindrical specimens), indirect tensile strength test (21 cylindrical specimens) and flexural bending test (21 beam specimens). The results revealed that, more asphalt content needed as the fibers length and concentration increased. The fatigue life estimation depending on cyclic load to failure in the beam test support the idea that polyester fibers really improve the resistance of fatigue cracking since the repetitions to failure increased by 9.40 % for the 0.50 % of 12.70 mm fibers length. Both of Marshall stability and indirect tensile strength suffer from slight reduction in their values, whereas, the 0.75 % of 12.70 mm fibers length caused lowering in Marshall stability and indirect tensile strength by 11.70 % and 6.00 % respectively.